Acute gastrointestinal bleeding due to primary aortoduodenal fistula: Report of two rare cases - Ufuk TÜTÜN,; Ayşen AKSÖYEK,; Ahmet Tulga ULUS,; Ali İhsan PARLAR,; M. Kamil GÖL,; Murat BAYAZIT, (Turkish Journal of Gastroenterology, 2019)
-